(untitled) (MATEMATIKA, 2018)
An existence result of multiple solutions for a class of two-point fractional boundary value equations depending upon a positive parameter is established. Our main tool is a three critical points theorem due to Bonanno and Marano [G. Bonanno and S.A. Marano,On the structure of the critical set of non-differentiable functions with a weak compactness condition, Appl. Anal. 89 (2010), 1-10].